The first Tornado in Nepal: March 2019 - Jha, Tribhuvan Chandra (Journal of General Practice and Emergency Medicine of Nepal, 2019)
On March 2019, first tornado was observed in Nepal. Bara and Parsa was two district that faced the disaster. As patient started to come into the hospital, we had shortage of medicine and space. We managed the surge of patient with triaging, first line treatment and referral of the critical patients. There were many crush and cut injuries and most of the critically ill patient had head injury and hypothermia.